Management Accounting in The State Forestry: The Example of Poland - Joanna PIŁACIK (Communications of International Proceedings, 2023)
The majority of forests in Poland are owned by the State Treasury and managed by the State Forest Holding, referred to as the State Forests. This entity fulfills the statutory obligation of conducting sustainable forest management, aiming to preserve the sustainability of forests, maintain the multifunctional use of forests, and increase forest resources. Within this framework, State Forests incur specific costs for the implementation of environmental and social tasks. The current accounting system of State Forests, generating financial information, lacks tools to correlate the costs of economic activities with the specific natural, economic, and social conditions and the outcomes of their operations (revenues and financial results). This study aims to present the managerial accounting system, using the specific example of the State Forest Holding in Poland. Additionally, key elements of this system will be highlighted in the context of conducting forest management in line with the principles of sustainable development. To achieve the purpose of the study, the author used the technique of comparative content analysis of secondary data, literature review and direct observations.
Keywords: accounting in the state forestry; management accounting; The State Forests National Forest Holding